High-Q-value borate microwave dielectric ceramic material as well as preparation method and application thereof

Preparation of (Zn1-xMgx)2.99Li0.02(BO3)2 borate microwave dielectric ceramic material through low-temperature sintering process, solving the problem of easy decomposition of traditional borate materials at high temperatures, and achieving high Q value and low dielectric Ceramic material with electrical constant is suitable for 5G and 6G communications, and has environmentally friendly and efficient production characteristics.

CN119191818AActive Publication Date: 2024-12-27ZHAOQING UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411336017.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

Existing borate-based microwave dielectric ceramic materials are prone to decomposition at high temperatures, affecting their performance and reliability. In addition, traditional solid-phase synthesis methods are not environmentally friendly and difficult to meet the development trend of low-cost, high-efficiency and environmentally friendly.

Method used

Prepare (Zn1-xMgx)2.99Li0.02(BO3)2 borate microwave dielectric ceramic material by low-temperature sintering process. Through specific ball milling, drying, crushing and sintering steps, the sintering temperature is reduced and the microstructure is optimized to improve the material. density and dielectric properties.

Benefits of technology

Achieve high Q value and low dielectric constant ceramic materials, reduce dielectric loss and temperature drift coefficient, improve the density and grain uniformity of the material, and is suitable for 5G and 6G mobile communications and other fields, and is environmentally friendly and efficient. Production characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191818A_ABST
    Figure CN119191818A_ABST
Patent Text Reader

Abstract

The invention provides a high-Q-value borate microwave dielectric ceramic material as well as a preparation method and application thereof. The chemical composition expression of the ceramic material is (Zn < 1-x > Mg < x >) < 2.99 > Li < 0.02 > (BO < 3 >) < 2 >, and x is equal to 0.01 to 0.1. The preparation method comprises the following steps: according to chemical composition requirements of the ceramic material, carrying out primary ball milling on a Zn source, a Mg source, a Li source and a B source to obtain preformed powder, carrying out drying, crushing, presintering and cooling processes on the preformed powder to obtain prefabricated powder, carrying out ball milling, secondary drying, granulation, secondary crushing and molding on the prefabricated powder to obtain a molded sample, and sintering the molded sample according to a sintering temperature curve to obtain the ceramic material. The ceramic material is obtained. The relative density of the (Zn1-xMgx) 2.99 Li0.02 (BO3) 2 ceramic material is up to 98% or above, and the (Zn1-xMgx) 2.99 Li0.02 (BO3) 2 ceramic material has the characteristics of high Q value and low dielectric constant, and can be applied to information communication materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microwave dielectric ceramic materials, and in particular relates to a high-Q value borate microwave dielectric ceramic material, a preparation method and an application thereof. Background Art

[0002] In today's rapidly developing wireless communication field, the rapid advancement of science and technology has continuously refreshed the rate and efficiency of signal transmission. With the increasing requirements of communication systems for high speed and high stability, the research and application of microwave dielectric ceramics as core components are receiving more and more attention. This type of material has excellent dielectric properties such as low dielectric constant, high Q value and temperature variation coefficient, and is expected to achieve fast and stable signal transmission, providing material support for the practical application of 5G and 6G mobile communications. Microwave dielectric ceramics have extremely important applications in communication equipment. In addition to being able to make core components such as dielectric resonators, filters, and antennas, they also have special physical properties, which are of great significance for improving communication quality, reducing signal interference, and reducing device size. With the development of wireless communication technology, people's demand for microwave dielectric materials is also increasing. There is an urgent need to study new material formulations, preparation processes and innovative design methods to meet the growing market demand.

[0003] In this context, borate-based microwave dielectric ceramic materials with extremely low dielectric constants have attracted much attention. This type of material has potentially important application value in the field of 5G communications, but there are still many problems with its preparation method. Conventional solid-phase synthesis methods are prone to decomposition of borates at high temperatures, which seriously affects its performance and reliability, leading to its application in industrial production. Therefore, the development of new low-temperature sintering processes, the exploration of new environmentally friendly materials, and the optimization of their microstructures are the current research focuses at home and abroad.

[0004] In the future wireless communication era, microwave dielectric ceramics will still play an important role. At the same time, under the development trend of low cost, high efficiency and environmental protection, the research and development of microwave dielectric materials will pay more attention to environmental protection and social benefits in the future development of communication technology, so that communication technology can develop in a "green" direction.

[0005] In summary, this application aims to provide new microwave dielectric materials in the fields of information communication and the like by developing new structures, new methods and new processes for microwave dielectric materials. Summary of the invention

[0006] In order to solve the above problems in the prior art, the present invention provides a high-Q value borate microwave dielectric ceramic material and a preparation method and application thereof.

[0007] The first aspect of the present invention provides a borate microwave dielectric ceramic material, the chemical composition expression of the ceramic material is (Zn 1-xMg x ) 2.99 Li 0.02 (BO3)2; x = 0.01-0.1. The value of x can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1, and any value between any two point values.

[0008] In some specific examples, the density of the ceramic material is 4.0-4.5 g / cm 3 , the density can be 4.0, 4.1, 4.2, 4.3, 4.4 or 4.5, as well as any value between any two point values.

[0009] In some specific examples, the Q×f of the ceramic material is 12000-175000 GHz. The dielectric loss can be 12000-80000 GHz, 80000-120000 GHz, 120000-150000 GHz or 150000-175000 GHz. Q×f is the product of the inverse of the dielectric loss (quality factor Q) and the frequency (f), and is used to evaluate the performance of microwave dielectric ceramics.

[0010] In some specific examples, the resonance temperature drift coefficient of the ceramic material is -29ppm / °C to -89ppm / °C. The resonance temperature drift coefficient may be -29ppm / °C to -40ppm / °C, -40ppm / °C to -60ppm / °C, or -60ppm / °C to -89ppm / °C.

[0011] In some specific examples, the dielectric constant of the ceramic material is 6.8 to 7.3. The dielectric constant may be 6.8 to 7.0 or 7.0 to 7.3.

[0012] In some specific examples, the grain size of the ceramic material is 0.7-3.6 μm. The grain size may be 0.7-1.2 μm, 1.2-1.8 μm, 1.8-2.4 μm, 2.4-3.2 μm or 3.2-3.6 μm.

[0013] In some specific examples, the Zn source in the ceramic material is Zn oxide, the Mg source is Mg oxide, the Li source is Li salt (such as Li carbonate), and the B source is B oxide. In a specific example, the Zn source is ZnO, the Mg source is MgO, the Li source is Li2CO3, and the B source is B2O3.

[0014] In some specific examples, the purity of the Zn source, Mg source, Li source and B source in the ceramic material is greater than 99.5%. Preferably, the purity of the Zn source, Mg source, Li source and B source is greater than 99.9%.

[0015] A second aspect of the present invention provides a method for preparing a borate microwave dielectric ceramic material, comprising the following steps:

[0016] 1) According to the chemical composition requirements of the ceramic material, Zn source, Mg source, Li source and B source are weighed respectively, and the first ball milling is performed to obtain a preformed powder;

[0017] In some feasible examples, the ball milling medium of the first ball milling is zirconium ball milling medium.

[0018] In some feasible examples, in the first ball milling, the speed of the ball mill ranges from 300 to 650 rpm, and the ball milling time is 12 to 32 hours. The speed is selected according to needs, and is generally preferably 400 to 450 rpm. The ball milling time can generally be 12 to 18 hours, 18 to 24 hours, or 24 to 32 hours.

[0019] In some feasible examples, in the first ball milling, the ball milling solvent is water, and the mass ratio of the total powder, the zirconium ball milling medium and the water is 1:2:3.5 to 1:2.5:4. It can be 1:2:3.5 to 1:2:4 or 1:2.5:3.5 to 1:2.5:4.

[0020] 2) subjecting the preformed powder to a drying, a grinding, a pre-sintering and a cooling process to obtain a preformed powder;

[0021] In some feasible examples, the primary drying temperature is 80-100° C., and the primary drying time is 10-24 hours. The drying time can be 10-16 hours or 16-24 hours.

[0022] In some feasible examples, the particle size of the once-crushed powder is 30-60 meshes. The particle size can be 30, 40, 50 or 60 meshes. And any value between any two point values.

[0023] In some feasible examples, the pre-sintering method is to heat up to 780-840°C at a heating rate of 2-5°C / min, keep the temperature for 3-4 hours, then cool down to 80-120°C at a cooling rate of 2-5°C / min, and then anneal. The heating rate and the cooling rate are generally kept consistent, which can be 2, 3, 4, or 5°C / min. The heating temperature can be 780-800°C, 800-820°C, or 820-840°C. The cooling temperature can be 80-100°C or 100-120°C. The annealing is to anneal to room temperature.

[0024] 3) ball milling the preformed powder for a second time, and then drying, granulating, crushing and molding the preformed powder for a second time to obtain a molded sample;

[0025] In some feasible examples, in the second ball milling, the ball milling solvent is water, and the mass ratio of the total powder, the zirconium ball milling medium and the water is 1:2:3.5 to 1:2.5:4. It can be 1:2:3.5 to 1:2:4 or 1:2.5:3.5 to 1:2.5:4.

[0026] In some feasible examples, in the second ball milling, the speed of the ball mill is in the range of 300 to 600 rpm, and the ball milling time is 12 to 32 hours. The speed is selected according to the needs, and is generally preferably 400 to 485 rpm. The ball milling time can generally be 12 to 18 hours, 18 to 24 hours, or 24 to 32 hours.

[0027] In some feasible examples, the secondary drying temperature is 80-100° C., and the secondary drying time is 10-24 hours. The secondary drying time is 10-24 hours. The drying time can be 10-16 hours or 16-24 hours.

[0028] In some feasible examples, granulation is performed by adding 10 to 20 wt% of the total mass of the powder to the secondary dried powder. The polymeric binder can be a polyvinyl alcohol binder, and the amount added can be 10 wt%, 15 wt% or 20 wt%, which is specifically selected according to the bonding conditions. The particle size of the polymeric binder is 120 to 200 meshes to improve the viscosity of the powder, make it easy to form, and reduce the pores. The powder with the added binder is screened through a 120 to 200 mesh sieve to make the powder more delicate and play a granulation role, and the particle size of the binder is preferably 150 to 200 meshes.

[0029] In some feasible examples, in step 3), the particle size of the powder after secondary grinding is 100-120 meshes. The particle size can be 100, 110 or 120 meshes.

[0030] In some feasible examples, the molding is to press-mold the powder after secondary grinding to obtain a molded sample. Specifically, the diameter of the molded sample is 5 to 6 mm and the height is 10 to 12 mm;

[0031] In some specific examples, the pressure molding uses an oil press, the pressure is 2-5MPa, the pressure speed is 100-200mm / s, and the mold removal pressure is 8-12MPa. The pressure can be 2, 3, 4 or 5MPa, and the pressure speed can be 100-120mm / s, 120-140mm / s, 140-160mm / s, 160-180mm / s or 180-200mm / s. The mold removal pressure can be 8, 9, 10, 11, 12MPa.

[0032] 4) Sintering the molded sample according to a sintering temperature curve to obtain the ceramic material.

[0033] In some specific examples, the sintering temperature curve is: 4-1) the molded sample is heated from 25 to 35 ° C to 500 to 550 ° C at a rate of 2 to 5 ° C / min, and kept warm for 3 to 4 hours; 4-2) the temperature is increased at a rate of 2 to 5 ° C / min to 825 to 925 ° C, and kept warm for 3 to 4 hours; 4-3) the temperature is reduced to 80 to 120 ° C at a rate of 2 to 5 ° C / min, and then naturally cooled to room temperature to obtain a ceramic material. The starting temperature is room temperature, which can generally be 25 to 35 ° C. The heating rate and the cooling rate are generally maintained consistent, which can be 2, 3, 4, or 5 ° C / min. The first heating rate can be 500 to 520 ° C or 520 to 550 ° C. The second heating rate is 825 to 850 ° C, 850 to 875 ° C or 875 to 925 ° C. The cooling temperature can be 80 to 100 ° C or 100 to 120 ° C. Cooling is cooling to room temperature.

[0034] The third aspect of the present invention provides a borate microwave dielectric ceramic material prepared by the above preparation method.

[0035] A fourth aspect of the present invention provides the use of the above-mentioned borate microwave dielectric ceramic material or the borate microwave dielectric ceramic material prepared by the above-mentioned preparation method in information communication materials, such as in dielectric resonators, filters, and antennas.

[0036] The present invention has the following technical effects including but not limited to:

[0037] 1) The present invention (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 ceramic material, the relative density is up to 98% or more, with high Q value and low dielectric constant, and Mg + Substitute Zn in small proportion + No secondary phase is formed in the Zn3B2O6 system, and its performance is not destroyed but improved. The grain size is obvious and the grain size is uniform in a specific ratio.

[0038] 2) The present invention adopts low temperature sintering technology, which is different from the traditional solid phase process. + By lowering the sintering temperature on the basis of replacement, the temperature drift coefficient is one step closer to zero compared with the original research, and it has the two major performance characteristics of low loss and low dielectric constant. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 For the invention examples 1, 2, 3, and 4, (Zn 1-x Mg x ) 2.99 Li 0.02Spectral comparison of XRD patterns of (BO3)2 microwave ceramic materials, ZnO, and Zn3(BO3)2;

[0040] Figure 2 For the invention examples 3, 5, and comparative examples 1 and 2, (Zn 1-x Mg x ) 2.99 Li 0.02 Spectral comparison of XRD patterns of (BO3)2 microwave ceramic materials, ZnO, Mg2B2O5, and Zn3(BO3)2;

[0041] Figure 3 (Zn prepared in Examples 1, 2, 3, 4, 5 of the present invention and Comparative Examples 1 and 2 1-x Mg x ) 2.99 Li 0.02 SEM spectrum of (BO3)2 microwave ceramic material, where (A) is (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (B) is (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (C) is (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (D) is (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (E) is (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (F) is the (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (G) is the (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material.

[0042] Figure 4 For the (Zn prepared in Examples 1, 2, 3, 4, 5 and Comparative Examples 1 and 21-x Mg x ) 2.99 Li 0.02 Average grain size distribution diagram of (BO3)2 microwave ceramic material, where (a) is the (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (b) (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (c) (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (d) (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (e) (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (f) is the (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material, (g) is the (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2 microwave ceramic material.

[0043] Figure 5 It is a comparison chart of Q×f and relative density of inventive embodiments 1, 2, 3, and 4. DETAILED DESCRIPTION

[0044] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0045] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0047] The numerical values ​​of decimal points in this application are designed to have an error of ±0.01 inevitably.

[0048] Example 1

[0049] (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2(x=0.01), the preparation method specifically comprises the following steps:

[0050] 1-1) Weighing and preparing materials: The raw materials are Li2CO3, B2O3, MgO, and ZnO, and the purity is about 99.9%. When x=0.01, the total weight is 80g, and Li2CO3 weighs 0.189g, B2O3 weighs 17.83g, MgO weighs 0.31g, and ZnO weighs 61.677g.

[0051] 1-2) First ball milling: The mass ratio of the total powder, zirconium ball milling medium and pure water is 1:2:3.5 and mixed into a ball mill container. The speed of the ball mill is 450 rpm and the ball milling time is 24 hours.

[0052] 2-1) Primary high-temperature drying: Filter out the zirconium balls from the mixed slurry and pour it into a long iron basin, place it in a drying oven at a constant temperature of 95°C and dry it for about 12 hours.

[0053] 2-2) Primary grinding: The dried powder is crushed and finely ground with a grinding rod, and the particles are sieved through a 40-mesh screen to obtain powder.

[0054] 2-3) Powder pre-sintering: The initial sintering temperature is 825°C, and the temperature is raised from room temperature to 825°C at a heating rate of 5°C / min, and then kept at this temperature for 3 hours. Then it is cooled to 100°C at the same rate, and then naturally cooled to room temperature to obtain pre-made powder.

[0055] 3-1) Secondary ball milling: The pre-milled powder was ball milled again, and the rolling ball mill was carried out at a speed of 455 rpm for 24 hours. The ball milling conditions were the same as the primary ball milling.

[0056] 3-2) Secondary high-temperature drying: Pour into a container and bake in a constant temperature box at 95°C for about 12 hours until dry.

[0057] 3-3) Sieving and granulating: After drying, crush and grind the powder, add 20wt% polyvinyl alcohol polymer binder based on the total weight of the powder, and the particle size of the polyvinyl alcohol polymer binder is 200 meshes.

[0058] 3-4) Dry pressing: The sample is molded into a size of 11mm in diameter and 5mm in height. The powder is weighed and poured into a stainless steel mold with a diameter of 11mm. The mold is placed in the center of the hydraulic press platform. The downward pressure conditions are set to 2MPa, 150mm / s, and 12MPa for demolding.

[0059] 4) Sintering: The pressed block is loaded into a ceramic crucible and placed in a heating furnace. The program is set to start from about 30°C in the furnace, and the temperature is raised at a rate of 4°C / min to 500°C to start the first colloid discharge, and the heat preservation time is 4 hours. Then the temperature is raised to 900°C at a rate of 4°C / min and kept at this temperature for 3 hours; the temperature is cooled down at a rate of 4°C / min to 100°C, and then cooled spontaneously to obtain the final sample.

[0060] Polishing test: The microwave dielectric ceramic material (Zn 1-x Mg x ) 2.99 Li 0.02 The sample surface of (BO3)2 was quickly polished with a polishing machine, and the smooth plane had better contact with the parallel plate resonant cavity mold, making it easy to measure dielectric properties such as dielectric constant, and Q×f.

[0061] Example 2

[0062] (Zn 1-x Mg x ) 2.99 Li 0.02 A method for preparing a microwave dielectric ceramic material by sintering (BO3)2 (x=0.03) at 900°C, specifically comprising the following steps:

[0063] Each step is basically the same as that of Example 1, except that the weight of the chemical formula in step (1-1) is different. 1-x Mg x ) 2.99 Li 0.02 (BO3)2(x=0.03) is weighed. The raw materials are Li2CO3, B2O3, MgO and ZnO with a purity of about 99.9%. When x=0.03, the total weight is 80g, including 0.19g Li2CO3, 17.97g B2O3, 0.93g MgO and 60.91g ZnO.

[0064] Example 3

[0065] (Zn 1-x Mg x ) 2.99 Li 0.02 A method for preparing a microwave dielectric ceramic material by sintering (BO3)2 (x=0.05) at 900°C, specifically comprising the following steps:

[0066] Each step is basically the same as that of Example 1, except that the weight of the chemical formula in step (1-1) is different. 1-x Mg x ) 2.99 Li 0.02 (BO3)2(x=0.05) is weighed. The raw materials are Li2CO3, B2O3, MgO and ZnO with a purity of about 99.9%. When x=0.05, the total weight is 80g, including 0.191g Li2CO3, 18.11g B2O3, 1.57g MgO and 60.13g ZnO.

[0067] Example 4

[0068] (Zn 1-x Mg x ) 2.99 Li 0.02 A method for preparing a microwave dielectric ceramic material by sintering (BO3)2 (x=0.07) at 900°C, specifically comprising the following steps:

[0069] Each step is basically the same as that of Example 1, except that the weight of the chemical formula in step (1-1) is different. 1-x Mg x ) 2.99 Li 0.02(BO3)2(x=0.07) is weighed. The raw materials are Li2CO3, B2O3, MgO and ZnO with a purity of about 99.9%. When x=0.07, the total weight is 80g, including 0.194g Li2CO3, 18.26g B2O3, 2.21g MgO and 59.34g ZnO.

[0070] Example 5

[0071] (Zn 1-x Mg x ) 2.99 Li 0.02 A method for preparing a microwave dielectric ceramic material by sintering (BO3)2 (x=0.1) at 900°C, specifically comprising the following steps:

[0072] Each step is basically the same as that of Example 1, except that in step (1-1), the chemical formula ratio is different. In this case, (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2(x=0.1) is weighed: the raw materials are Li2CO3, B2O3, MgO and ZnO with a purity of about 99.9%. When x=0.1, the total weight is 80g, including 0.196g Li2CO3, 18.48g B2O3, 3.2g MgO and 58.13g ZnO.

[0073] Comparative Example 1

[0074] Each step is basically the same as that of Example 1, except that in step (1-1), the chemical formula ratio is different. In this case, (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2(x=0.15) is weighed. The raw materials are Li2CO3, B2O3, MgO and ZnO with a purity of about 99.9%. When x=0.15, the total weight is 80g, including 0.2g Li2CO3, 18.86g B2O3, 4.9g MgO and 56.04g ZnO.

[0075] Comparative Example 2

[0076] Each step is basically the same as that of Example 1, except that in step (1-1), the chemical formula ratio is different. In this case, (Zn 1-x Mg x ) 2.99 Li 0.02(BO3)2(x=0.2) is weighed. The raw materials are Li2CO3, B2O3, MgO and ZnO with a purity of about 99.9%. When x=0.2, the total weight is 80g, including 0.21g Li2CO3, 19.26g B2O3, 6.67g MgO and 53.86g ZnO.

[0077] like Figure 1 As shown, the XRD images of Examples 1 to 4 show that they are composed of two phases, ZnO (PDF#36-1451) and the main phase Zn3(BO3)2 (PDF#71-2063). As the value of x increases, the amount of ZnO decreases and the crystallinity decreases. The diffraction peak in the direction of the crystal plane index (402) shifts to the right as the value of x increases, which also corresponds to the change in the unit cell volume. As x increases, the volume decreases. Figure 5 As shown, the trends of Q×f of Examples 1 to 4 are consistent with the relative density, indicating that Q×f of Examples 1 to 4 are closely related to the density.

[0078] Figure 3 (A) is the SEM image of Example 1, Figure 4 (a) is the average grain size distribution diagram of Example 1, Figure 5 The figure is a comparison chart of Q×f and relative density of Example 1. Figure 4 In (a), it can be seen that the average grain size is 1.84826μm, below 10% is 1.2145μm, below 50% is 1.7948μm, and below 90% is 2.4299μm. The grains are large and small, and there are many pores. The density obtained by Archimedes test is 4.21429g / cm 3 .from Figure 5 It can be seen that the relative density is 98.16% and Q×f is 31489.63GHz. The dielectric properties are tested and calculated by a 26.5GHz network analyzer, ε r is 6.8983,τ f It is -30.489ppm / ℃.

[0079] Figure 3 (B) is the SEM image of Example 2, Figure 4 (b) is the average grain size distribution diagram of Example 2. Figure 3 Middle (B) and Figure 4 In (b), it can be seen that the grain size has increased, the pores have decreased, the average grain size is 2.47837μm, the 10% below is 1.4051μm, the 50% below is 2.1864μm, and the 90% below is 2.9466μm. Although the average grain size has increased, it can be seen that the grain size difference is not large, and the grain distribution is uniform. Density 4.24138g / cm 3 .from Figure 5 It can be seen that the relative density is as high as 98.68%, and Q×f is 170512.35GHz. Excellent various factors make it have excellent dielectric properties of ε r is 6.9348,τ f It is -62.65ppm / ℃.

[0080] Figure 3 (C) is the SEM image of Example 3, Figure 4 (c) is the average grain size distribution diagram of Example 3. Figure 3 In (C), a small number of large grains can be seen protruding, the average grain size is 2.32118μm, less than 10% is 0.8423μm, less than 50% is 1.8423μm, less than 90% is 3.3288μm, and the uniformity of grain distribution is slightly reduced. Density 4.19355g / cm 3 .from Figure 5 It can be seen that the relative density is 97.95%, Q×f is 16101.74GHz, and its dielectric properties are ε r is 6.9595,τ f It is -70.298ppm / ℃.

[0081] Figure 3 (D) is the SEM image of Example 4, Figure 4 In (d), the average grain size distribution diagram of Example 4 shows a small number of large grain protrusions. The average grain size is 2.39527 μm, less than 50% is 1.8703 μm, and less than 90% is 3.522 μm. Most of the grains are large. Figure 5 It can be seen that the relative density is 96.67% and Q×f is 12234.48GHz. The density is 4.13793g / cm3. The low density and large particle size have implications for the material properties. Its dielectric properties are ε r is 7.244,τ f It is -88.54ppm / ℃.

[0082] like Figure 2 As shown, the XRD pattern of Example 5 still includes two phases: ZnO (PDF#36-1451) and the main phase Zn3(BO3)2 (PDF#71-2063), indicating that other phases have not been introduced to affect the performance when x=0.1. Figure 3 (E) SEM shows that the large-sized grains appear in Examples 3 and 4. Figure 4It can be seen from (e) that the average grain size is 2.42256 μm, below 10 percent is 0.9084 μm, below 50 percent is 2.0615 μm, and below 90 percent is 3.8873 μm. The uniformity of grain distribution is lower than that of Examples 1-4.

[0083] like Figure 2 As shown, the XRD images of Comparative Example 2 (x = 0.15) and Comparative Example 2 (x = 0.2) show that the three phases are composed of ZnO (PDF#36-1451), Mg2B2O5 (PDF#09-3360) and the main phase Zn3(BO3)2 (PDF#71-2063). The appearance of the third phase of Mg2B2O5 causes a sharp drop in performance parameters, from Figure 3 In (F) and (G), there are obvious long needle-shaped particles, and there are more particles. Figure 4 (f) of Comparative Example 2 Figure 4 (f) The average grain size is 2.30448 μm, less than 10% is 1.2154 μm, less than 50% is 2.1463 μm, and less than 90% is 3.4276 μm. Figure 4 In (g), it can be seen that the average grain size of Comparative Example 2 is 2.42283μm, below 10% is 1.3025μm, below 50% is 2.1674μm, and below 90% is 3.2244μm. The interior is distributed with larger grains, and the emergence of new phases increases the pores, resulting in poor microwave properties.

[0084] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A borate microwave dielectric ceramic material, characterized in that: The chemical composition expression of the ceramic material is (Zn 1-x Mg x ) 2.99 Li 0.02 (BO3)2; x = 0.01 ~ 0.

1.

2. The borate microwave dielectric ceramic material according to claim 1, characterized in that: The density of the ceramic material is 4.0-4.5 g / cm 3 ; and / or, the Q×f of the ceramic material is 12000 to 175000 GHz; And / or, the resonance temperature drift coefficient of the ceramic material is -29ppm / °C to -89ppm / °C; And / or, the dielectric constant of the ceramic material is 6.8 to 7.

3.

3. The borate microwave dielectric ceramic material according to claim 1, characterized in that: The Zn source in the ceramic material is Zn oxide, the Mg source is Mg oxide, the Li source is Li salt, and the B source is B oxide; And / or, the purity of the Zn source, Mg source, Li source and B source in the ceramic material is greater than 99.5%; And / or, the grain size of the ceramic material is 0.7-3.6 μm.

4. The borate microwave dielectric ceramic material according to claim 3, characterized in that: The purity of the Zn source, Mg source, Li source and B source is greater than 99.9%; And / or, the Zn source in the ceramic material is ZnO, the Mg source is MgO, the Li source is Li2CO3, and the B source is B2O3.

5. The method for preparing the borate microwave dielectric ceramic material according to any one of claims 1 to 4, comprising the following steps: 1) According to the chemical composition requirements of the ceramic material, Zn source, Mg source, Li source and B source are weighed respectively, and the first ball milling is performed to obtain a preformed powder; 2) subjecting the preformed powder to a drying, a grinding, a pre-sintering and a cooling process to obtain a preformed powder; 3) ball milling the preformed powder for a second time, and then drying, granulating, crushing and molding the preformed powder for a second time to obtain a molded sample; 4) Sintering the molded sample according to a sintering temperature curve to obtain the ceramic material.

6. The preparation method according to claim 5, characterized in that: The ball milling media for the first and second ball milling are both zirconium ball milling media; And / or, in step 1), during the first ball milling, the speed of the ball mill is in the range of 300 to 650 rpm, and the ball milling time is 12 to 32 hours; In step 2), the primary drying temperature is 80-100° C. and the primary drying time is 10-24 hours; And / or, in step 2), the powder is crushed once to a particle size of 30 to 60 mesh; And / or, in step 2), the pre-sintering method is to heat up to 780-840°C at a heating rate of 2-5°C / min, keep the temperature for 3-4 hours, then cool down to 80-120°C at a cooling rate of 2-5°C / min, and then anneal.

7. The preparation method according to claim 6, characterized in that: In the first ball milling, the ball milling solvent is water, and the mass ratio of the total powder, the zirconium ball milling medium and the water is 1:2:3.5 to 1:2.5:4; And / or, in the second ball milling, the ball milling solvent is water, and the mass ratio of the total powder, the zirconium ball milling medium and the water is 1:2:3.5 to 1:2.5:

4.

8. The preparation method according to claim 5, characterized in that: In step 3), during the second ball milling, the speed of the ball mill is in the range of 300 to 650 rpm, and the ball milling time is 12 to 32 hours; And / or, in step 3), the secondary drying temperature is 80-100° C., and the secondary drying time is 10-24 hours; And / or, in step 3), granulation is performed by adding 10 to 20 wt % of a polymer binder based on the total mass of the powder to the secondary dried powder for granulation; and / or, in step 3), the particle size of the powder after secondary crushing is 100-120 mesh; And / or, in step 3), the forming is to pressure-form the powder after the second grinding to obtain a molded sample; And / or, in step 4), the sintering temperature curve is: 4-1) heating the molded sample from 25-35°C to 500-550°C at a rate of 2-5°C / min, and keeping it warm for 3-4 hours; 4-2) heating the molded sample at a rate of 2-5°C / min to 825-925°C, and keeping it warm for 3-4 hours; 4-3) cooling the molded sample to 80-120°C at a rate of 2-5°C / min, and then naturally cooling it to room temperature to obtain a ceramic material.

9. The preparation method according to claim 8, characterized in that: The polymer adhesive is a polyvinyl alcohol adhesive; and / or, the particle size of the polymeric adhesive is 120 to 200 mesh; and / or, the diameter of the molded sample is 10 to 12 mm and the height is 5 to 6 mm; And / or, the pressure molding adopts an oil hydraulic press with a downward pressure of 2 to 5 MPa, a downward pressure speed of 100 to 200 mm / s, and a mold removal pressure of 8 to 12 MPa.

10. Use of the borate microwave dielectric ceramic material according to any one of claims 1 to 4 and the borate microwave dielectric ceramic material prepared by the preparation method according to any one of claims 5 to 9 in information communication materials.

Citation Information

Patent Citations

  • Low-dielectric constant high-quality factor LTCC microwave medium material and preparation method thereof

    CN107434411A

  • Microwave dielectric ceramic material as well as preparation method and application thereof

    CN111807831A

  • Preparation method of cold sintering-assisted low-temperature densification of Zn3B2O6 microwave ceramic materials

    CN114933468A

  • Microwave dielectric ceramic and preparation method thereof

    CN116947480A

  • Silicate-based low-temperature sintered microwave dielectric ceramic material and preparation method therefor

    WO2023159896A1